Advances in biostimulants as an integrated pest management tool in horticulture - Dara, Surendra K. (Burleigh Dodds Series in Agricultural Science, 2021)
This chapter covers the definition of biostimulants, brief summary of various categories, and how they are used for promoting plant growth, building soil structure, imparting stress tolerance, and contribute to pest and disease suppression. Strategies for using biostimulants as a part of IPM and some challenges and future opportunities were also discussed.